The impact of knowledge management practices on organizational performance ]A field study on agricultural and development NGOs in the Gaza Strip] In the period from 2010-2020 AD - Abu Hatab, Ghassan Ahmad (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to examine the reality of knowledge management practices and their impact on the institutional performance of agricultural and development NGOs in the Gaza Strip, through conducting a case study of the three largest institutions working in the fields of agriculture and development in the period between 2010-2020. The study was based on the hypothesis that there is a significant effect of knowledge management practices represented by (knowledge management processes, knowledge management leadership, knowledge management culture, knowledge management technology, and knowledge management measurement) on the institutional performance of agricultural and development NGOs in the Gaza Strip. Census Method (also known as the Complete Enumeration Survey Method) was used to collect data from 252 workers in the institutions under investigation, namely, agricultural relief, agricultural work committees, and development work center "MAAN. The study employed the descriptive analytical approach, the case study approach, and the participatory qualitative approach. The researcher used the questionnaire as a key tool for data collection. The study found that an evidence existed for a significant effect of (knowledge management culture, knowledge management technology, and knowledge management measurement) on institutional performance, whereas no evidence was found for a significant effect of (knowledge management processes and knowledge management leadership) on institutional performance. In addition. The main recommendation of study are: to provide a continuous training for employees during their career path, to show a continuous encouragement for employees and beneficiaries to present new creative ideas, to encourage employees’ initiatives for promoting the culture of knowledge management toward the enhancement of their institutional performance attributed to their job tasks, to optimize the use of internet in the context of achieving the agricultural and development NGOs goals.